Design and Development of a Special Service Tools Sliding Hammer for Removing Injector Nozzles on the SAA4D125E Diesel Engine - Ari Aryadi; Reza Febriano Armas; Budi Utomo Wisesa (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
This research focuses on designing a specialized tool called Special Service Tools Nozzle Attachment with a Sliding Hammer to remove injector nozzles in diesel engines. The fact that the long cycle time in the manual removal process of injector nozzles can be streamlined through this tool is emphasized. The researcher designed and developed this tool with the assistance of CAD. The research results show that by using this tool, the cycle time for removing injector nozzles can be reduced from 23 minutes to just 13 minutes. This indicates a significant improvement in work efficiency and productivity. This research has important implications for the industry, especially in the maintenance and repair of diesel engines. Penelitian ini berfokus untuk merancang-bangun sebuah alat khusus yang disebut Special Service Tools Nozzel Attachment dengan Sliding Hammer untuk melepas injector nozzle pada mesin diesel. Fakta bahwa cycle time yang lama dalam pengerjaan proses pelepasan injector nozzle yang dilakukan secara manual diharapkan dapat di efisiensikan melalui alat ini. Peneliti merancang dan mengembangkan alat ini dengan bantuan CAD. Hasil penelitian menunjukkan bahwa dengan menggunakan alat ini, cycle time untuk melepas injector nozzle dapat ditekan dari 23 menit menjadi hanya 13 menit. Hal ini menunjukkan peningkatan yang signifikan dalam efisiensi waktu pengerjaan dan produktivitas hal ini memiliki implikasi penting dalam industri, terutama dalam perawatan dan perbaikan mesin diesel.